Analisis Bibliometrik Perkembangan Riset Digital Marketing dan Kecerdasan Buatan dalam Mewujudkan Strategi Bisnis Berkelanjutan di Era Industri 4.0 - Nofanda Dwi Putra; Lissa Rosdiana Noer (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to examine the development of Digital Marketing and Artificial Intelligence research in the context of Sustainable Business Strategy in the Industry 4.0 Era through a bibliometric approach to 702 Scopus-indexed publications spanning from 1972 to the projected year 2025. A comprehensive analysis was conducted to identify the dynamics of publication trends, citation impact, international collaboration patterns, and the evolution of research focus. The research findings show a consistent increase in the number of publications, reaching a peak in 2024 with 19 publications. The strongest citation impact was found in articles published in 2020 with 817 citations. In terms of institutional affiliation, Universiti Teknologi Malaysia Kuala Lumpur stands out as the most prolific contributor with 4 papers, and the Business, Management, and Accounting study domain dominates the research landscape with a proportion of 45.6%. Mapping of international research collaborations shows strong ties between the United States (168 publications, 12,920 citations) and India (99 publications, 1,103 citations). Furthermore, research focus mapping using VOSviewer (a threshold of at least three keyword occurrences) indicates a shift from conventional themes to digital issues dominating recent publications, with topics such as artificial intelligence, machine learning, big data analytics, innovation, and sustainability marking rapidly evolving research directions. The implications of these findings emphasize the importance of a deep understanding of the integration of digital marketing and artificial intelligence in designing adaptive and sustainable business strategies, and open up opportunities for further research related to digital transformation and business innovation in the Industry 4.0 era.